Pre-Service Mathematics and Primary School Teachers’ Design and Application of Mathematics Materials in Woodworking Workshops - Demet DENİZ YILMAZ; Ayça KARTAL (Hayef: Journal of Education)
This study addressed in-class actvites with concrete mathematcs (math) materials developed by preservice math and primary school teachers in woodworking workshops and investgated what preservice teachers and primary and secondary school students thought about lectures with those materials. The study employed an embedded mixed design, a predominantly quanttatve approach. The sample consisted of 23 preservice math and primary school teachers and 30 secondary school and primary school students in Turkey. Quanttatve data were collected using the Torrance Test of Creatve Thinking Test. Qualitatve data were collected using a Material Design Evaluaton Rubric and a Semi-Structured Interview Form. The results showed that the woodworking workshops improved the fgural creatvity of the preservice math teachers and both the fgural and verbal creatvity of the preservice primary school teachers. The preservice teachers had no idea about what woodworking workshops were and had difculty mostly with sandpapering and cutng. The primary and secondary school students stated that they enjoyed using the math materials and learned beter. In line with the results of the research, it can be suggested that woodworking workshops be expanded not only in universites but also in primary and secondary schools.